Impact of dividend policy on Stock choice decision of retail investors in India: An Empirical Study (International Journal of Food and Nutritional Sciences, 2021)
For investors, dividends serve as both a source of knowledge and a source of cash flow. An important factor in investing selections is the dividend prediction offered by management. For investors, a dividend is an indication of a company's sound management and the possibility of further development in the future. Share prices are positively affected by frequent dividend payments, according to the relevance theory of dividends. Companies that consistently pay substantial dividends continue to be the preferred investment option. For quite some time, dividend policy has piqued the curiosity of academics studying economics. According to the current school of thought in finance, one of the primary roles of the financial management is to decide on dividend policy with the goal of increasing the wealth of shareholders. Revenue, net profit, other income, stock price, and market capital were among the factors that the research used to analyze the link between dividend and each sample company's dividend policy. Graphs, tables, the observation method, and basic linear connection analysis of variance were among the statistical tools and methods used for the research. We obtained some intriguing outcomes using these tools and procedures. Regarding the sample firms' payout policies and the correlation between dividends and NP, RS, OI, and stock price, the results were contradictory.